The Effect of Natural Antioxidants on Bond Strength of Composite Resin To Tooth Structure Post Internal Bleaching: Pengaruh antioksidan alami terhadap kekuatan ikatan resin komposit dengan struktur gigi pasca pemutihan internal - Febrianty Alexes Siampa; Juni Jekti Nugroho; Hafsah Katu (Makassar Dental Journal PDGI Makassar, 2023)
Internal bleaching is a non-vital bleaching tooth method performed after endodontic treatment of discolored teeth, by the applica-tion of strong oxidator agents in pulp chamber. Internal bleaching agents can have adverse effects, one of which is the reduced bond strength of the composite resin with the tooth structure. There are various types of antioxidants that can improve bond strength after internal bleaching procedures, generally synthetic antioxidant ingredients. Besides that, many antioxidants from na-tural plant extracts have been developed, such as green tea extract, pine bark, rosemary, pomegranate peel and grape seed. The objective of this article is to improve knowledge about antioxidant materials that can be used to increase the bond strength of composite resin on the tooth structure after internal bleaching. The use of bleaching agents has been shown to reduce the bond strength of composite resin after internal bleaching. Researchers have focus on plant extracts to develop a non-toxic, biocompa-tible and effective antioxidant protocol which can be safely applied to oxidized tooth structures. It is concluded that there are various kinds of antioxidants materials from natural plant extracts which can be used in dentistry to increase the bond strength of composite resin on the tooth structure after internal bleaching.